[Letter to president Clinton regarding the increase in the cigarette tax] - ROBB,CS (Tufts Archival Research Center, 2007)
Letter from Senator Charles S. Robb to President Clinton, urging him to take into account the disproportionate burden an increase in the cigarette tax will have on lower income families as well as the tobacco industry, which is one of the largest employers in the South. Disagrees with the use of this tax to be the primary means of funds for healthcare reform.